PENGEMBANGAN MEDIA PEMBELAJARAN AMPLOP PINTAR UNTUK MENINGKATKAN KEMENARIKAN BELAJAR SISWA KELAS IV DI SDN KETAWANGGEDE KOTA MALANG - Yuliani, Fatkhiyah Nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
This study developed the Smart Envelope Learning Media for the Pancasila Education subject, specifically focusing on the topic of Indonesia's Diversity, to enhance student interest and engagement in learning. Having engaging and relevant learning media is crucial to support an effective learning process. This visual media is expected to serve as a more effective alternative compared to standard school textbooks, which, based on preliminary studies conducted in the fourth-grade class at SDN Ketawanggede, Malang, were found to be less engaging due to the abundance of text and unappealing images. Additionally, the use of the lecture method by teachers often made students feel bored and less actively involved. This research adopted the Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The study involved 25 fourth-grade students from SDN Ketawanggede as research subjects. Data collection techniques included observation, interviews, questionnaires, and documentation, utilizing instruments such as expert validation sheets and student response sheets. The validation process was conducted by media, material, and learning experts, yielding scores of 93%, 98%, and 95%, respectively, indicating that the learning media is highly valid and suitable for use in teaching. Furthermore, the student response questionnaire showed a very high level of interest, with an average score of 95.3%. This research and development study aims to (1) describe the development process of the Smart Envelope Learning Media based on the ADDIE model, and (2) evaluate the level of interest and effectiveness of the media in increasing student engagement. The Smart Envelope Media is expected to contribute positively by enhancing the learning experience and creating a more interactive and enjoyable learning atmosphere for students. ABSTRAK Penelitian ini mengembangkan Media Pembelajaran Amplop Pintar untuk mata pelajaran Pendidikan Pancasila, khususnya pada materi Keragaman Indonesia, khususnya pada materi Keragaman Indonesia, sebagai upaya meningkatkan minat dan kemenarikan belajar siswa. Memiliki media pembelajaran yang menarik dan sesuai dengan materi sangat penting untuk mendukung proses pembelajaran yang efektif. Media visual ini diharapkan dapat menjadi alternatif yang lebih efektif dibandingkan penggunaan buku paket sekolah, yang berdasarkan hasil studi awal di kelas IV SDN Ketawanggede Kota Malang, dinilai kurang menarik karena berisi banyak teks dan gambar yang kurang interaktif. Selain itu, metode ceramah yang masih digunakan guru cenderung membuat siswa cepat bosan dan kurang terlibat secara aktif. Penelitian ini mengadopsi metode Research and Development (R&D) dengan menggunakan model ADDIE, yang terdiri dari lima tahapan: analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek uji coba penelitian ini adalah 25 siswa kelas IV SDN Ketawanggede. Data dikumpulkan melalui teknik observasi, wawancara, angket, dan dokumentasi, dengan instrumen berupa lembar validasi ahli dan lembar respon siswa. Proses validasi melibatkan ahli media, materi, dan pembelajaran, yang memberikan hasil masing-masing sebesar 93%, 98%, dan 95%, menunjukkan bahwa media pembelajaran ini sangat valid dan layak digunakan dalam proses pembelajaran. Selain itu, hasil angket respon siswa menunjukkan tingkat kemenarikan yang sangat tinggi, dengan rata-rata 95,3%. Penelitian dan pengembangan ini bertujuan untuk (1) mendeskripsikan proses pengembangan Media Pembelajaran Amplop Pintar berbasis model ADDIE, dan (2) mengevaluasi tingkat kemenarikan serta efektivitas media dalam meningkatkan minat belajar siswa. Media Amplop Pintar ini diharapkan dapat memberikan kontribusi positif dalam meningkatkan pengalaman belajar siswa dan menciptakan suasana belajar yang lebih interaktif serta menyenangkan.This study developed the Smart Envelope Learning Media for the Pancasila Education subject, specifically focusing on the topic of Indonesia's Diversity, to enhance student interest and engagement in learning. Having engaging and relevant learning media is crucial to support an effective learning process. This visual media is expected to serve as a more effective alternative compared to standard school textbooks, which, based on preliminary studies conducted in the fourth-grade class at SDN Ketawanggede, Malang, were found to be less engaging due to the abundance of text and unappealing images. Additionally, the use of the lecture method by teachers often made students feel bored and less actively involved. This research adopted the Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The study involved 25 fourth-grade students from SDN Ketawanggede as research subjects. Data collection techniques included observation, interviews, questionnaires, and documentation, utilizing instruments such as expert validation sheets and student response sheets. The validation process was conducted by media, material, and learning experts, yielding scores of 93%, 98%, and 95%, respectively, indicating that the learning media is highly valid and suitable for use in teaching. Furthermore, the student response questionnaire showed a very high level of interest, with an average score of 95.3%. This research and development study aims to (1) describe the development process of the Smart Envelope Learning Media based on the ADDIE model, and (2) evaluate the level of interest and effectiveness of the media in increasing student engagement. The Smart Envelope Media is expected to contribute positively by enhancing the learning experience and creating a more interactive and enjoyable learning atmosphere for students.